The flow of axonal information among hippocampal sub-regions 2: patterned stimulation sharpens routing of information transmission - Lassers, Samuel Brandon; Vakilna, Yash S.; Tang, William C.; Brewer, Gregory J. (Frontiers in Neural Circuits, 2023)
The subregions of the hippocampal formation are essential for episodic learning and memory formation, yet the spike dynamics of each region contributing to this function are poorly understood, in part because of a lack of access to the inter-regional communicating axons. Here we reconstructed hippocampal networks confined to four subcompartments in 2D cultures on a multi-electrode array that monitors individual communicating axons. In our novel device, somal and axonal activity were measured simultaneously with the ability to ascertain the direction and speed of information transmission. Each subregion and inter-regional axons had unique power-law spiking dynamics, indicating differences in computational functions, with abundant axonal feedback. After stimulation, spiking and burst rates decreased in all subregions, spikes per burst generally decreased, intraburst spike rates increased, and burst duration decreased, which were specific for each subregion. These changes in spiking dynamics post-stimulation were found to occupy a narrow range, consistent with the maintenance of the network at a critical state. Functional connections between the subregion neurons and communicating axons in our device revealed homeostatic network routing strategies post-stimulation in which spontaneous feedback activity was selectively decreased and balanced by decreased feed-forward activity. Post-stimulation, the number of functional connections per array decreased, but the reliability of those connections increased. The networks maintained a balance in spiking and bursting dynamics in response to stimulation and sharpened network routing. These plastic characteristics of the network revealed the dynamic architecture of hippocampal computations in response to stimulation by selective routing on a spatiotemporal scale in single axons.